Efisiensi Pengelolaan Tempat Tidur Rawat Inap Berdasarkan Grafik Barber Jhonson di RS X Lampung - Marsim, Etanaulia; Setiawan, Susilo; Dwiyovita, Rizka; Bahri, Yessiana Luthfia; Latifah, Rif'at Mukhidatul; Annisa, Syifa (Politeknik Negeri Jember, 2025)
The imbalance in bed utilization across several inpatient units at Hospital X poses challenges to service efficiency, such as prolonged waiting times and an increased risk of nosocomial infections. This study aims to evaluate the efficiency of bed management at Hospital X in 2024 using the Barber Johnson Graph method. This research employed a quantitative descriptive design using secondary data obtained from daily inpatient census reports. The analyzed indicators included Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), and Bed Turn Over (BTO). The results showed a BOR of 75.91%, an AvLOS of 2.91 days, a TOI of 0.92 days, and a BTO of 95.56 times per year. Based on the Barber Johnson Graph, only BOR and BTO met the efficiency standards, while AvLOS and TOI were below the standard. These findings indicate that although bed occupancy levels and usage frequency were optimal, the relatively short length of stay and rapid bed vacancy intervals require further evaluation. This study provides valuable insights for hospital management in formulating policies to sustainably optimize inpatient service efficiency.